2012
DOI: 10.1007/s12560-012-9096-7
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Torque Teno Virus (TTV) in Tap Water in Public Schools from Southern Brazil

Abstract: Torque teno virus (TTV) was surveyed in tap water collected in schools from three municipalities located in the south of Brazil. TTV genomes were found in 11.7 % (4/34) of the samples. TTV DNA was detected in 10.5 % (2/19) of the samples collected at the city of Caxias do Sul and in 25 % (2/8) of the samples from Pelotas. Those cities have a low rate of sewage treatment. All samples from Santa Cruz do Sul, which has nearly 92 % of its sewage treated, were negative. These results suggest that the amount of sewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“… 18 In southern Brazil, studies showed a high prevalence of the virus in healthy donors (73.3%) in the municipality of Pelotas, RS 21 and also the presence of the virus in samples of drinking water and sewage water. 13 , 22 …”
Section: Discussionmentioning
confidence: 99%
“… 18 In southern Brazil, studies showed a high prevalence of the virus in healthy donors (73.3%) in the municipality of Pelotas, RS 21 and also the presence of the virus in samples of drinking water and sewage water. 13 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…A number of peculiarities, such as ubiquity and pervasiveness, make TTV an ideal model for studies of environmental survival and spread. Accordingly, TTV is frequently found in wastewater (38e100%), drinking water (5e12%) [27,28] and river water [29,30]. Again, because of its extremely high resistance to known inactivation procedures, TTV testing may be particularly useful after wastewater is subjected to treatment or cleaning procedures with the aim of evaluating the efficiency of these procedures in microbe removal.…”
Section: Ttv As a Marker Of Anthropic Pollutionmentioning
confidence: 99%
“…Surprisingly, despite being derived from a “closed” herd with no exposure to outside animals, a majority of the swine samples in our study were positive for huTTV DNA (Table 2). While exact estimates of the extent of contamination of water sources within the U.S with huTTV DNA are not available, extensive contamination has been reported in other parts of the world1618. Moreover, huTTV DNA has been previously detected in buffalo milk31.…”
Section: Discussionmentioning
confidence: 99%
“…Widespread environmental contamination, based on the detection of human TTV (huTTV) DNA, is extremely common in water sources161718, sewage19 and in air or on surfaces, especially in hospitals20. Contamination of swine-derived laboratory enzymes such as trypsin and some veterinary vaccines with TTSuVs is also reported21.…”
mentioning
confidence: 99%